MANAGEMENT OF THE QUALITY OF WATER RESOURCES FOR SUSTAINABLE DEVELOPMENT BASED ON INDUSTRIAL AND MANUFACTURING ENGINEERING - Andrey G. Paptsov; Karolina Yu. Popova (International Journal for Quality Research, 2022)
The goal of this paper is to justify the prospects and develop recommendations for consistent management of the quality of water resources for sustainable development based on industrial and manufacturing engineering, while taking into account the specific features of developed and developing countries. The originality of the research is that water resources are considered in terms of quality, and a consistent scientific view of the quality of water resources is formed for the first time in the unity of all its signs. It is suggested to use the methodology of comprehensive quality measurement which is being tested using the example of developed and developing countries in 2020. The uniqueness of the paper consists in the development of a new, non-financial approach to managing the quality of water resources, one that would involve reliance on industrial and manufacturing engineering in the digital economy. The novel nature of the research consists in examining the experience of developed and developing countries in order to identify and take into account their specific features and to develop specific highly-refined application-specific recommendations to ensure high efficiency management of the quality of water resources. In order to improve the quality of water resources in developed countries, it is recommended that e-government is developed by 95.74 per cent, and the active use of Big Data and analytics is increased by 96 per cent. In developing countries, it is recommended that the degree of robots distribution is increased by 96.02 per cent.